Effects of checkpoint inhibitors in advanced non-small cell lung cancer at population level from the National Immunotherapy Registry. (February 2020) - Smit, H.J.M.; Aerts, J.; van den Heuvel, M.; Hiltermann, T.J.N.; Bahce, I.; Smit, E.F.; Dingemans, A-M.C.; Hendriks, L.E.; Stigt, J.A.; Schramel, F.M.N.H.; van Tinteren, H.; Groen, H.J.M.; et al.
Highlights: Introduction of immunotherapy did not change quality of care between hospitals. Patients underrepresented in trials received immunotherapy in routine practice. Patients with brain metastases survived as long as those without this disorder. Patients with selected auto immune disorders survived longer. Abstract: Objective: Phase III studies of checkpoint inhibitors changed the therapeutic landscape for lung cancer. In 2015 the Dutch Society of Chest Physicians (NVALT) introduced a national immunotherapy registry for patients with lung cancer; quality standards for hospitals were implemented. At population level we studied clinical benefit in daily practice and in patients who are underrepresented in phase III trials. Materials and Methods: From the initial introduction of checkpoint inhibitors in the Netherlands patients were centrally registered. Educational programs and quality control were provided under supervision of NVALT. The largest immunotherapy providing hospitals were compared to hospitals who provided less checkpoint inhibitors as marker of experience. Patients characteristics, treatment and side effects, response rate and survival were studied. Results: A total of 2676 patients were registered, 2302 with follow up data were evaluated. Between October 2015 and December 2017 a gradual increase from 12 to 30 qualified hospitals showed no major toxicity differences. Toxicity led to a hospital admission rate of 9.1 with an average duration of 10.4 days. Overall tumor response was 21.8 % and median overall survival 12.6 months. Overall survival was not significantly different for patients aged ≥ 75 years, those having brain metastases or selected auto-immune diseases before start checkpoint inhibitors compared to younger patients or those without, respectively. Survival outcomes were worse in patients with PS 2+, non-smokers, and patients who received any palliative radiotherapy (HR 2.1, 95 % CI 1.7–2.7; 1.3, 95 % CI 1.0–1.6 and 1.2, 95 % CI 1.1–1.4, respectively). Conclusions: Changes in the therapeutic landscape did not lead to major differences in quality of care between hospitals. Elderly patients, those with brain metastases or selected auto-immune disease underrepresented in clinical trials did not do worse on checkpoint inhibitors, except for those with PS 2 + .